An unusual case of rapidly progressing glomerulonephritis in pregnancy; "triple positivity" or a co incidence? - Smita Divyaveer; Vaibhav Tiwari; Malagouda Patil; Chetan Mahajan; Tanima Das Bhattacharya; Avinandan Banerjee; Koushik Bhattacherjee; Arpita Raychaudhury; Rajendra Pandey (Society of Diabetic Nephropathy Prevention, 2017)
Background: Renal failure in pregnancy is usually due to acute kidney injury and very uncommonly due to rapidly progressing glomerulonephritis (RPGN). We describe here a case of RPGN in the first trimester of pregnancy. Case Presentation: A 26 years old female patient in first trimester of pregnancy presented with RPGN. Investigations revealed dual serological positivity of anti-neutrophil cytoplasmic antibody (ANCA) and anti-glomerular basement membrane antibody (anti-GBM). The biopsy showed crescentic glomerulonephritis with linear with IgG deposition on GBM as well as mesangial IgA deposition. Despite aggressive therapy with cyclophosphamide and plasma exchange she continued to be dialysis dependent and developed end-stage renal disease. Conclusions: RPGN is an uncommon cause of renal failure in pregnancy. While the dual ANCA and anti-GBM are common in RPGN and this concurrent occurrence is wellknown, however, the association of ANCA and IgA nephropathy has been described rather uncommonly. This rare case has positivity of all three in pregnancy.